A Method of License Plate Recognition Based on BP Neural Network with Median Filtering. (May 2019) - Li, Miaomiao; Miao, Zhenjiang; Wang, Jiaji; Wang, Shengbo; Zhang, Yuanhao
Abstract: With the rapid increase of cars, the research of license plate recognition in intelligent traffic algorithm has attracted much attention. In this paper, pointing at the shortcomings of the existing recognition algorithm, we adopt a license plate recognition method based on BP neural network with a median filtering. The method consists of a median filtering algorithm for denoising and a BP neural network for training and testing. First the character library is processed by median filtering to remove the influence of noise. Then, utilizing the strong learning ability of BP, the character library is passed into the network for classification. Compared with the traditional algorithm, our method not only speeds up the recognition efficiency, but also obtains more robust results. Therefore, the proposed approach can provide a technical support for the practical application of license plate recognizing.